An Earth increasingly full of uncertainties - Abd Razak, Dzulkifli (2008)
On April 22, the world celebrated Earth Day, a global environmental event which began in 1970. Around the world, millions of people gathered to show their support to mark the day that has increasingly become significant to the people of this earth. Today, the concern has gone beyond the mundane issues of air and water pollution, toxic dumps, pesticide abuses, or destruction of flora and fauna. Our attention is drawn to the issue of oil prices which now stands at more than US$110 (RM345) per barrel.